IMPROVING TEACHERS’ ABILITY IN DESIGNING SYLLABUS AND LESSON PLAN THROUGH PROFESSIONAL COACHING WITH A COOPERATIVE APPROACH AT MTSN 5 WEST ACEH SEMESTER 1 OF ACADEMIC YEAR 2018/2019 - Cut Anina; Yulidar Yulidar; Marsita Marsita (FKIP Universitas Al Washliyah Medan, 2018)
A research on improving teachers’ abilities in designing syllabus and lesson plan through professional coaching with a cooperative approach at MTsN 5 West Aceh in semester 1 of the 2018/2019 school year. This type of research was an action research with 4 stages, namely planning, implementation, observation and reflection. The research subjects were 8 teachers of MTsN 5 West Aceh in semester 1 of the 2018/2019 academic year. Data collection techniques were carried out by observation and documentation activities. Data validation used triangulation techniques. Data analysis used descriptive techniques. The results showed that there was an increase in the ability of teachers in designing syllabus and lesson plan from an average score of 49.59 with the criterion of a low score in the initial conditions, to 69.98 with the criterion of a moderate score in the first cycle and to 89.47 with the criterion of a very high score. good in the second cycle. The conclusion was that the professional coaching with a cooperative approach was proven to be able to improve teachers' abilities in designing syllabus and lesson plans at MTsN 5 West Aceh in semester 1 of the 2018/2019 school year.